THE IMPACT OF EXTENSIVE READING ON VOCABULARY ACQUISITION AND LEXICAL DIVERSITY IN EFL LEARNERS' WRITING - Hikmatova Charos,; Kattaboyeva Dilrabo Kattaboyevna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This study investigates the impact of extensive reading on vocabulary acquisition  and  lexical  diversity  in  EFL  learners’  writing.  Through  standard presentation to wealthy and changed writings, learners create more grounded word acknowledgment, more profound lexicon information, and an expanded capacity to utilize differing lexical things in composed errands. The discoveries show that broad perusing not as it were upgrades lexical run but moreover makes strides in general composing  quality.  The  consider  concludes  that  joining  broad  perusing  into  EFL programs  is  an  compelling  approach  to  cultivating  more  progressed  and  shifted composed dialect.